Optimal Multiple FCLs Allocation Considering DG Penetration in Meshed Network With Multi-Level Voltages - M. Hosseinpour; J. Sadeh (Iranian Journal of Electrical and Electronic Engineering, 2020)
Increasing the short circuit current due to the penetration of distributed generations (DGs) in various voltage levels and meshed topology is a basic problem in power systems. Using fault current limiter (FCL) is an efficient approach to mitigate the exceeded short circuit levels. In this paper, a new approach is presented for multiple FCLs locating to decrease short circuit levels in meshed networks with several subsystems and multi-level voltages. Modified hybrid genetic algorithm (GA) and sensitivity analysis (SA) are used to determine the type, number, location, and voltage level of FCLs. Also, an effective sensitivity index is proposed, which can reduce the search space for optimal allocation. This method suggests the optimal allocation with the least investment cost in multi-level voltages networks according to the FCL costs. The proposed method is evaluated in the IEEE 30-bus, 57-bus, and 300-bus test systems. Numerical results indicate the accuracy and efficiency of the proposed method.